Gender Equality In The Qur’an (A Critical Study Of M. Quraish Shihab’s Interpretation In Tafsir Al Misbah) - Nasution (CV PUTRA PUBLISHER, 2025)
This study examines gender equality within the family from the perspective of the Qur’an, focusing on a critical analysis of M. Quraish Shihab’s interpretation in *Tafsir Al-Misbah*. The background to this research stems from differing interpretations of Qur’anic verses concerning relations between men and women, which in some cases have led to gender inequality within family life. This study aims to analyse the concept of gender equality in the Qur’an, examine Quraish Shihab’s method of interpretation, and identify the implications of his thinking for Muslim family relations. This study employs a qualitative approach using library research. Data were collected through a review of the Qur’an, exegetical works, and relevant literature, and were subsequently analysed using descriptive-analytical methods and a critical approach. The findings indicate that, according to Quraish Shihab, the Qur’an affirms the equality of men and women in human, spiritual, and moral aspects. Any differences are understood as functional, not hierarchical. In his interpretation, Quraish Shihab employs a contextual, linguistic, and moderate approach, resulting in an understanding that emphasises the principles of justice, reciprocity (mubadalah), and partnership within the family.